HUBUNGAN ANTARA INTENSITAS PENGGUNAAN JARINGAN KOMUNIKASI DENGAN POLA GAYA HIDUP MASYARAKAT MENGARE, BUNGAH, GRESIK - Dimas Mahendra Putra; Nur Indah Dwi Prasetyaningsih; Asri Agustina; Rio Kurniawan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study investigates the correlation between the intensity of communication network usage and lifestyle patterns among the coastal community of Mengare, Bungah, Gresik. Using a quantitative approach with an explanatory survey method, data were collected from 20 respondents through structured questionnaires. The results show that daily use of the internet, social media, and messaging apps is prevalent. Most respondents use digital media for information, entertainment, and economic activities. The study found a significant correlation between communication network usage and lifestyle changes, including consumption behavior, leisure activities, social interaction, and digital economic aspirations.